A study on the factors that influence corporate reputation at university: A case study at University Malaysia Kelantan / Mohd Faizul Mohd Nor - Mohd Nor, Mohd Faizul (2011)
The aim of this study was to examine the factors that contribute to corporate reputation towards university, focusing upon University Malaysia Kelantan, Pengkalan Chepa, Kelantan. There are three factors being studied, which were: emotional appeal, products and services, and corporate social responsibility. As University Malaysia Kelantan had been chosen as the unit of analysis for this study, the researcher intend to discover a performance of the institution and figure it in the eyes of consumer. Therefore, several suggestions could be provided to University Malaysia Kelantan in improving their reputation in order to be a one of the most famous education institution in Malaysia. The researcher used both secondary and primary data in order to collect data. Moreover, questionnaires had been used in order to get feedback from the customers. The researcher had distributed 100 questionnaires and had gotten back 100 respondents’ feedback. The data collected was then tested on its reliability, then further analyzed using frequency analysis, descriptive—mean tests and Pearson Correlation Coefficient. Besides, Regression Analysis was used to test the hypothesis in this study. The findings of this paper suggest that all the factors are significant factors in explaining corporate reputation at University Malaysia Kelantan. The researcher suggests some recommendations are based from the results obtained in this study, the researcher hope it can help University Malaysia Kelantan to improve their image and reputation